2012
DOI: 10.1590/s0004-282x2012000300017
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphopsia associated with topiramate for migraine prevention

Abstract: pyramidal syndrome characterized by incomplete hemiparesis on the right hemibody. Myotatic exalted reflexes in the right hemibody and plantar-cutaneous reflex were indifferent. DiSCuSSionReviewing the relevant literature worldwide, Labrune syndrome was considered as a possible diagnosis for the present case 2 . Despite the presence of cysts, calcification, and edema of the white substance found in our patient, suggesting neurocysticercosis, equinecocosis 3 or neoplasia, there was no serologic or histopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…In conclusion, we believe that, along with other drugs, TPM use should be added to the differential diagnosis of visual illusions in migraineurs or non-migraineurs either. Nonetheless, we endorse the notion that the underlying migraine in a vast proportion of TPM consumers can substantially predispose them to these symptoms 1,3,4 .…”
Section: Dear Editorssupporting
confidence: 66%
See 4 more Smart Citations
“…In conclusion, we believe that, along with other drugs, TPM use should be added to the differential diagnosis of visual illusions in migraineurs or non-migraineurs either. Nonetheless, we endorse the notion that the underlying migraine in a vast proportion of TPM consumers can substantially predispose them to these symptoms 1,3,4 .…”
Section: Dear Editorssupporting
confidence: 66%
“…It is important to underline that the authors reported a positive dechallenge test that corroborates a causal relationship between TPM and such an adverse effect 1,6 . Nevertheless, in their final conclusion on the etiology of such an association, they stated that "because it may occur in the aura of migraines, these visual illusions are likely to be a result of the migraine" 1 . Indeed, one of the leading TPM indications is prevention of migraine attacks and herein comes the uncertainty of whether illusions are linked to migraine or to TPM use.…”
Section: Dear Editorsmentioning
confidence: 66%
See 3 more Smart Citations